The role and implications of big data on strategic management accounting practices: a case study in a Malaysian manufacturing company / Nik Herda Nik Abdullah, Soliha Sanusi and Enni Savitri - Nik Abdullah, Nik Herda; Sanusi, Soliha; Savitri, Enni (Universiti Teknologi MARA, 2022)
This research aimed to analyze the role and implications of big data on strategic management accounting practices in the manufacturing industry. The research was conducted in Shah Alam, Selangor, Malaysia. This research used a qualitative approach, with data being gathered through indepth interviews, observations, and the review of documents. The interviews revealed that big data facilitates and improves the implementation of strategic management accounting practices on competitors’ and customers’ analyses and costing by streamlining the analysis process, decreasing time spent searching for data, increasing data accuracy, and assisting in the decision-making process, which leads to better forecasts and improved company profitability. This conclusion was further confirmed by content analysis of the documents reviewed. The study contributes to the literature on strategic management accounting and big data, with a focus on the manufacturing industry. Additionally, the findings of this study indicate that strategic management accounting is the key source of acceptable and pertinent information for management at all levels. The implications arising from this research affect both practitioners and researchers concerning the importance of incorporating big data into strategic management accounting processes in order to enhance analysis and provide a better outcome.